Factors of Successful E-Petitions in Policy Making Process: A Scoping Review - Wahyuningrat Wahyuningrat; Denok Kurniasih; Paulus Israwan Setyoko (Indonesian Association for Public Administration, 2023)
Efforts to continue to increase public participation in policymaking continue to be carried out as a step toward a more open government. Along with the popularity of online petitions (e-petitions) initiated by various lines of society, a systematic analysis was carried out to find out how successful an online petition (e-petitions) is as a public space in policy making. We try to provide a new perspective from a broader side of the previous partial research. This indicator of success is based on the original purpose for which the petition was published. As a result, there are three important things that are divided into two scopes of paths for achieving goals. First, the way of communication in which there is a linguistic approach is an important factor that influences how information from the petition is conveyed to the public and leads to the publicity of the petition. Second, the way of delivery is the basis for how the voice of the community is conveyed to policymakers, which is influenced by the political will of a region. Finally, media attention is a factor between the two scopes, which have dual roles as a â€œtoaâ€ to the public, and a messenger of policy. This review is expected to be a reference for initiators who propose policies from the community as well as a consideration for policymakers to actively involve the community's role in the policymaking process.